Concept Analysis of Sound Wave Physics in Tabuhan Cave Rocks - Dea Nur Umiel Agustina; Rif'ati Dina Handayani; Sri Handono Budi Prastowo (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2023)
Indonesia is a plural country with a diverse population and culture. Cultural diversity in Indonesia can be an important capital for the progress of the nation. One of them is the unique culture in Pacitan in the form of stones that can sound like the gamelan in Tabuhan Cave. Tabuhan Cave is a karst cave located at the western end of Pacitan and is included in 33 UNESCO sites. The purpose of this research is to analyze the physics concept of sound waves on the stone of Tabuhan Cave. The method used in this study is a qualitative method with data analysis techniques in the form of content analysis. The results of the analysis obtained are the physics of sound waves in the Tabuhan Cave rock caused by the rock structure and environmental conditions. The sound of the Tabuhan Cave stones has a frequency ranging from 900-1000 Hz and the sound intensity level is around -40 to -100 dB which is measured at different distances. The greater the distance, the smaller the frequency and intensity of the sounds of the Tabuhan Cave stones. So it can be concluded that there is a physics concept of sound waves on the Tabuhan Cave stone which is influenced by the characteristics of the stone, the position of the stone, the hitting point, and the distance used. The greater the distance from the Tabuhan Cave stone, the smaller the sound will be heard with the frequency and intensity that is increasingly small too.